Not When But Whether: Modality and Future Time Reference in English and Dutch. Issue 1 (19th January 2023) - Robertson, Cole; Roberts, Seán G.
Abstract: Previous research on linguistic relativity and economic decisions hypothesized that speakers of languages with obligatory tense marking of future time reference (FTR) should value future rewards less than speakers of languages which permit present tense FTR. This was hypothesized on the basis of obligatory linguistic marking (e.g., will ) causing speakers to construe future events as more temporally distal and thereby to exhibit increased "temporal discounting": the subjective devaluation of outcomes as the delay until they will occur increases. However, several aspects of this hypothesis are incomplete. First, it overlooks the role of "modal" FTR structures which encode notions about the likelihood of future outcomes (e.g., might ). This may influence "probability discounting": the subjective devaluation of outcomes as the probability of their occurrence decreases. Second, the extent to which linguistic structures are subjectively related to temporal or probability discounting differences is currently unknown. To address these, we elicited FTR language and subjective ratings of temporal distance and probability from speakers of English, which exhibits strongly grammaticized FTR, and Dutch, which does not. Several findings went against the predictions of the previous hypothesis: Framing an FTR statement in the present ("Ellie arrives later on") versus the future tense ("…will arrive…") did not affect ratings of temporal distance; English speakers rated future statements as relatively more temporally proximal than Dutch speakers; and English and Dutch speakers rated future tenses as encoding high certainty, which suggests that obligatory future tense marking might result in less discounting. Additionally, compared with Dutch speakers, English speakers used more low‐certainty terms in general (e.g., may ) and as a function of various experimental factors. We conclude that the prior cross‐linguistic observations of the link between FTR and psychological discounting may be caused by the connection between low‐certainty modal structures and probability discounting, rather than future tense and temporality.